Book reviews: Granite landscapes of the world, by Piotr Migoń, 2006. Oxford University Press, Oxford, UK, 384 pages. Hardback: price 383$, ISBN 0-19-927368-5; 978-0-19-927368-3 - Burda, Jolanta (Geologos, 2022)
No abstract available.